CuAl-LDH Modified with Filamentous Macroalgae for Anionic Dyes Removal: A Study on Selectivity, Adsorption Efficiency, and Regeneration - Wijaya, Alfan; Hanum, Laila; Melwita, Elda; Lesbani, Aldes (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Continuous modifications of Layered Double Hydroxides (LDH) materials are essential to enhance their structural stability and improve their capacity for pollutant adsorption, addressing the need for more effective remediation strategies in environmental applications. This research study has proposed the preparation of CuAl-LDH supported filamentous macroalgae of Spirogyra sp. (CuAl-LDH/SA) via coprecipitation and hydrothermal methods. The prepared CuAl-LDH/SA composites were investigated for the adsorption of direct yellow 12 (DY) and remazol red (RR) dyes in batch mode experiments. The structure and morphology of the prepared CuAl-LDH/SA were identified by X-ray Diffraction (XRD), Fourier Transform Infra Red (FT-IR), (Brunauer-Emmett-Teller) BET surface area, Thermogravimetry / Differential Thermal Analyzer (TG/DTA), and Scanning Electron Microscope (SEM). For the adsorption process, the effects of initial pH, contact time, initial concentration, temperature, adsorption selectivity, and adsorbent regeneration, as well as kinetics, isotherms, and thermodynamics were studied. The adsorption selectivity test resulted in the RR dye being more selective compared to DY. The maximum capacities for RR adsorption were 72.464 mg/g (pH = 2, 150 min, 303 K). CuAl-LDH/SA can be regenerated for 4 cycles with a percent removal of 29.32%. The adsorption process followed the intraparticle diffusion kinetics model and Langmuir isotherm. Thermodynamic studies showed that the adsorption of RR using CuAl-LDH/SA was endothermic and spontaneous. The results of this study indicate that CuAl-LDH/SA composite material shows potential material in the removal of anionic dyes from aqueous solutions. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).